Postrzeganie reklamy telewizyjnej produktów farmaceutycznych w świetle wyników badań bezpośrednich - Kraszkiewicz, Daria; Waniowski, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
There are numerous reasons for the very rapid increase in the consumption of medicines and other pharmaceuticals that has occurred in Poland in recent years. According to experts, these include easier access to these products, the ageing of Polish society, the development of lifestyle diseases requiring pharmacological treatment, the growing popularity of dietary supplements, as well as marketing activities of pharmaceutical companies. This last aspect is important, as the pharmaceutical industry is at the forefront of the most profitable and fastest growing sectors of the economies of highly-developed countries. It is probably the reason why currently extremely intense advertising campaigns conducted by large pharmaceutical companies can be observed on the Polish market. This paper attempts to define the perception of various aspects of television commercials of OTC drugs and dietary supplements and present various conditions of this process with particular emphasis on the psychological aspects. The results of our own study on the perception of OTC drugs and dietary supplement advertising and its impact on purchasing decisions are presented. On their basis, conclusions were drawn from the analysis of empirical material, indicating the impact of television advertising campaigns for medicines and other pharmaceuticals on the level and structure of their consumption.
Keywords: advertising; consumption; drugs